Thermoplastic polyimide resin with block structure and preparation method thereof

By designing the embedded segment structure thermoplastic polytamide resin, the soft segment of the hard segment and the flexible ether bond containing phenylmazole or amide units, combined with N-methyl-pyrodoltone and other solvents, solve the existing thermoplastic polyacide amine The problem of stress concentration in high temperature amine reactions realizes high -bonding strength, high -size stability and good mechanical properties.

CN119371660AActive Publication Date: 2025-01-28COMO (SHANGHAI) NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411930921.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing thermoplastic polyimide resins generate stress concentration in high-temperature imidation reaction, affecting the bonding strength and dimensional stability, and are difficult to meet the comprehensive performance requirements of the new FCCL or semiconductor frame protective film.

Method used

By designing the embedded segment structure thermoplastic polytamide resin, the soft segment of the hard segment and flexible ether bonds containing phenylzole or amide units, combined with N-methyl-pyrodidone and other solvents to avoid high temperature amine reactions, reduce bubbles Rate and form an excellent hydrogen bond network and micro -phase separation structure.

Benefits of technology

Achieve high adhesion strength, high -size stability, and good mechanical properties, and significantly improves the comprehensive performance of polytamide glue film composite copper foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371660A_ABST
    Figure CN119371660A_ABST
Patent Text Reader

Abstract

The invention relates to a thermoplastic polyimide resin with a block structure and a preparation method thereof, and a polyimide adhesive film and polyimide composite copper foil composed of the thermoplastic polyimide resin with the block structure. The polyimide adhesive film is formed by coating thermoplastic polyimide resin and thermosetting polyimide resin on a polyimide base film and mixing the thermoplastic polyimide resin and the thermosetting polyimide resin. Wherein the thermoplastic resin is composed of a hard segment containing a benzimidazole or amide unit and a soft segment containing a flexible ether bond. The polyimide adhesive film composite copper foil is prepared through rolling, mold pressing and other processing modes. The thermoplastic polyimide resin is of a soluble structure and does not need precursor processing, so that the formation of bubbles is effectively inhibited, and an IPN interpenetrating network structure is formed between the cured thermoplastic resin and thermosetting resin, so that the copper foil has excellent mechanical property, adhesive property and dimensional stability after being compounded; therefore, the method can be applied to the fields of semiconductor packaging, flexible copper-clad plates and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and particularly relates to a block structure thermoplastic polyimide resin and a preparation method thereof. Background Art

[0002] Polyimide film composite copper foil has important applications in the preparation of flexible copper clad laminates and semiconductor frame protective films. After composite, the two have key indicators such as peel strength, flexural strength and warpage, and the structure and performance of the adhesive layer on the surface of the polyimide film seriously affect the above indicators. Therefore, the development of the adhesive layer plays an important role in improving the comprehensive performance of this type of material.

[0003] At present, the widely used adhesive layer materials mainly include epoxy resin and thermoplastic polyimide resin. Epoxy resin is mainly used in the preparation of three-layer flexible copper clad laminate (3L-FCCL), while thermoplastic polyimide resin is mainly used in the preparation of two-layer flexible copper clad laminate (2L-FCCL), that is, glue-free FCCL. Relatively speaking, 2L-FCCL is thinner and more flexible, so it has better application prospects. However, the thermoplastic polyimide resin used in 2L-FCCL is mostly processed with polyamic acid precursors, which need to undergo high-temperature imidization and other processes. The small molecular water and residual solvent released in the imidization reaction will produce stress concentration, affecting the bonding strength and dimensional stability. For example, the invention patent with application number 202010136338.5 discloses a method for preparing a glue-free single-sided board by sequentially laminating a thermoplastic polyimide resin precursor (i.e., polyamic acid) and a thermosetting polyimide resin precursor. During the molding process, both resins need to undergo a high-temperature imidization reaction at 350-400°C. The invention patent with application number 202410829219.6 discloses a method for preparing a flexible copper clad laminate through a two-step imidization process, and the second imidization needs to be carried out under harsh conditions without oxygen, and the thermal imidization reaction time is 20-60 minutes. Therefore, how to directly synthesize a soluble thermoplastic PI resin through structural design, and to ensure the excellent dimensional stability of the resin layer in the polyimide adhesive film and its excellent bonding performance with the polyimide base film and copper foil is of great significance for the development of new FCCL or semiconductor frame protective films. Summary of the invention

[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a polyimide adhesive film composite copper foil having high bonding strength, high dimensional stability and other comprehensive properties.

[0005] The present invention is achieved through the following technical solutions: In the first aspect, a block structure thermoplastic polyimide resin is obtained by sequentially polymerizing a dianhydride monomer Ar with a diamine monomer R1 and a diamine monomer R2. The general structural formula of the resin is as follows: ; Wherein, the dianhydride monomer Ar is one of the following dianhydrides: ; The diamine monomer R1 is one of the following diamines: ; The diamine monomer R2 is one of the following diamines: ; Wherein, m=2-8 and n=2-8 of the block structure thermoplastic polyimide resin.

[0006] Preferably, the block structure thermoplastic resin is composed of a hard segment containing benzimidazole or amide units and a soft segment containing flexible ether bonds, and the molar fraction ratio of the hard segment is (30-50) mol%.

[0007] In a second aspect, a method for preparing a block structure thermoplastic polyimide resin comprises: dissolving a diamine monomer R1 and a diamine monomer R2 in a solvent, and reacting the diamine monomers with a dianhydride monomer Ar in batches.

[0008] Wherein, the solvent is selected from one or a combination of N,N-dimethylacetamide (DMAc), N-methyl-pyrrolidone (NMP) or γ-butyrolactone.

[0009] Preferably, the molar ratio of diamine monomer R1 to dianhydride monomer Ar is (m+1) / m.

[0010] Preferably, the molar ratio of diamine monomer R2 to dianhydride monomer Ar is n / (n+1).

[0011] Preferably, nitrogen or an inert gas is used to protect the process of dissolving the diamine monomer R1 and the diamine monomer R2 with a solvent and the reaction process.

[0012] Furthermore, the preparation method specifically comprises the following steps: S1, under nitrogen protection, dissolving the diamine monomer R1 in a solvent, stirring at room temperature, adding the dianhydride monomer Ar after complete dissolution, and controlling the molar ratio of the diamine / dianhydride monomer to be (m+1) / m, the reaction temperature to be (0-5)°C, the reaction time to be (6-12) h, and then raising the reaction temperature to (160-170)°C and reacting for (6-10) h to synthesize the polyimide resin I terminated with an amino group.

[0013] S2. Under nitrogen protection, dissolve the diamine monomer R2 in a solvent and stir at room temperature. After it is completely dissolved, add the dianhydride monomer Ar and control the molar ratio of diamine / dianhydride monomer to be n / (n+1). The reaction temperature is (0-5)°C and the reaction is carried out for (6-12) hours. Then, the reaction temperature is increased to (160-170)°C and the reaction is carried out for (6-10) hours to synthesize the polyimide resin II terminated with anhydride.

[0014] S3. Resin I and resin II are mixed under nitrogen protection, and the reaction temperature is controlled to be (0-20) °C for sufficient reaction for (6-12) h to obtain a viscous thermoplastic polyimide resin. After aging, filtering and degassing, the above-mentioned block structure thermoplastic polyimide resin is obtained.

[0015] In a third aspect, a resin composition comprises: the above-mentioned block structure thermoplastic polyimide resin and thermosetting polyimide resin, wherein the thermosetting resin is selected from any one of bismaleimide resin and PMR type polyimide resin or a combination of both.

[0016] Preferably, the mass fraction of the thermosetting polyimide resin in the resin composition is (10-20) wt %.

[0017] Preferably, the resin composition further comprises a solvent, and the solvent is selected from one or a combination of N, N-dimethylacetamide (DMAc), N-methyl-pyrrolidone (NMP) or γ-butyrolactone.

[0018] Preferably, the solid content of the resin composition is (10-15) wt %.

[0019] Preferably, the viscosity of the resin composition is 1500-3000 centipoise at 30°C.

[0020] In a fourth aspect, a method for preparing the above-mentioned resin composition comprises: fully mixing a block structure thermoplastic polyimide resin and a thermosetting polyimide resin.

[0021] Preferably, the preparation method further comprises: fully mixing the block structure thermoplastic polyimide resin and the thermosetting polyimide resin by mechanical stirring.

[0022] Furthermore, the block structure thermoplastic polyimide resin and the thermosetting polyimide resin are fully mixed and then filtered and degassed for later use.

[0023] In a fifth aspect, a polyimide adhesive film is provided, wherein the resin composition is coated on the surface of a polyimide base film by a cast extrusion method, and then the polyimide adhesive film is obtained by baking and drying.

[0024] Preferably, the coating amount of the resin composition in the polyimide film is (3-8) wt %.

[0025] Preferably, the baking temperature is 120-180°C.

[0026] Preferably, the coating thickness of the resin composition layer is controlled to be 3-8 μm by adjusting the roller speed and the extrusion amount.

[0027] In a sixth aspect, a polyimide film composite copper foil is obtained by composite the above-mentioned polyimide film and copper foil by rolling.

[0028] Preferably, the copper foil is surface pretreated with a dilute alkaline solution, and then the polyimide film and the copper foil are composited by rolling to obtain a polyimide film composite copper foil.

[0029] Preferably, the dilute alkaline solution is selected from one of KOH, NaOH or ammonia water, the concentration is 0.3-1.0 M, the pretreatment time is 1-3 min, and the temperature is 30-50 °C.

[0030] Preferably, the rolling temperature is 300-400° C., the rolling pressure is 0.5-1.0 kN, and the rolling speed is 1.0-1.5 m / min.

[0031] The beneficial effects achieved by the technical solution of the present invention are: The present invention adopts structural design, selects monomers containing rigid units such as benzimidazole and amide and flexible units such as ether bonds to synthesize a block structure thermoplastic polyimide resin with a certain degree of polymerization, uses solvents such as N-methyl-pyrrolidone and N, N-dimethylacetamide to dissolve the thermoplastic polyimide resin, avoids complex high-temperature imidization reaction after composite copper foil and the by-product water generated, and reduces the bubble rate in the composite process.

[0032] The benzimidazole and amide units in the synthetic thermoplastic resin can form a rich hydrogen bond network, thereby giving the resin composition system excellent bonding properties.

[0033] The microphase separation structure formed in the block structure thermoplastic polyimide resin gives the resin good melt softening behavior, so that it can be better composited with copper foil and polyimide-based film.

[0034] A block structure thermoplastic polyimide and a thermosetting polyimide resin are selected and mixed into a resin composition and used as a bonding layer. The interpenetrating network structure formed after curing allows the thermosetting resin to restrict the molecular chain movement of the thermoplastic resin, thereby giving the composite structure excellent dimensional stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1Schematic diagram of the structure of polyimide film composite copper foil. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0038] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.

[0039] The above-mentioned polyimide monomer is provided by Tianjin Zotye Materials Technology Co., Ltd.; the solvent is provided by Sinopharm Group; the polyimide base film is purchased from SKC Kolon of South Korea; and the thermosetting polyimide resin is provided by Sanhua Electronic Insulation Materials Co., Ltd.

[0040] The bonding strength was tested by the 90° peel strength test method of IPC-TM-650 2.4.9, the dimensional stability was measured by the IPC-TM-650 2.2.4 test method, and the tensile strength was measured by a universal material testing machine at a tensile rate of 5 mm / min.

[0041] Example 1 Under nitrogen protection, the diamine monomer 2-(4-aminophenyl)-5-aminobenzimidazole (4, 5-BIA) was dissolved in NMP, stirred at room temperature, and after it was completely dissolved, the dianhydride monomer 4,4'-oxydiphthalic anhydride (ODPA) was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 4 / 3, the reaction temperature was 5 ℃, the reaction was carried out for 12 h, and the reaction temperature was increased to 170 ℃ for 10 h to synthesize the polyimide resin I terminated with an amine group. Similarly, under nitrogen protection, the diamine monomer 3,4'-diaminodiphenyl ether (3, 4-ODA) was dissolved in NMP, stirred at room temperature, and after it was completely dissolved, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 3 / 4, the reaction temperature was 5 ℃, the reaction was carried out for 12 h, and the reaction temperature was increased to 170 ℃ for 10 h to synthesize the polyimide resin II terminated with anhydride. Resin I and resin II were mixed in equal molar ratios, and the reaction temperature was controlled at 20 ℃ under nitrogen protection for 12 h to obtain a viscous thermoplastic polyimide resin, which was fully matured, filtered, and degassed for use. The synthesized thermoplastic polyimide resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 15 wt%. After complete mixing, the mixture was degassed and set aside. The mixed resin was uniformly extruded and coated on the polyimide base film by casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0042] Example 2 Under nitrogen protection, the diamine monomer 2-(3-aminophenyl)-5-aminobenzimidazole (3, 5-BIA) was dissolved in NMP and stirred at room temperature. After it was completely dissolved, the dianhydride monomer 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (BTDA) was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 4 / 3. The reaction temperature was 5 ℃, and the reaction was carried out for 12 h. The reaction temperature was then increased to 170 ℃ for 10 h to synthesize the polyimide resin I terminated with an amine group. Similarly, under nitrogen protection, the diamine monomer APB was dissolved in NMP and stirred at room temperature. After it was completely dissolved, the dianhydride monomer BTDA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 3 / 4. The reaction temperature was 5 ℃, and the reaction was carried out for 12 h. The reaction temperature was then increased to 170 ℃ for 10 h to synthesize the polyimide resin II terminated with anhydride. Resin I and resin II were mixed in equal molar ratios, and the reaction temperature was controlled at 20 ℃ under nitrogen protection for 12 h to obtain a viscous thermoplastic polyimide resin, which was fully matured, filtered, and degassed for use. The synthesized thermoplastic polyimide resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 15 wt%. After complete mixing, the mixture was degassed and set aside. The mixed resin was uniformly extruded and coated on the polyimide base film by casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0043] Example 3 Under nitrogen protection, the diamine monomer 3,5-diaminobenzoic acid (DABA) was dissolved in γ-butyrolactone, stirred at room temperature, and after complete dissolution, the dianhydride monomer BTDA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 5 / 4, the reaction temperature was 0 ℃, the reaction was carried out for 12 h, and then the reaction temperature was increased to 170 ℃ for 10 h to synthesize the polyimide resin I terminated with an amine group. Similarly, under nitrogen protection, the diamine monomer APB was dissolved in γ-butyrolactone, stirred at room temperature, and after complete dissolution, the dianhydride monomer BTDA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 4 / 5, the reaction temperature was 5 ℃, the reaction was carried out for 12 h, and then the reaction temperature was increased to 170 ℃ for 10 h to synthesize the polyimide resin II terminated with anhydride. Resin I and resin II were mixed in equal molar ratios and reacted for 12 h under nitrogen protection at a reaction temperature of 20 ℃ to obtain a viscous thermoplastic polyimide resin, which was fully matured, filtered, and degassed for use. The synthesized thermoplastic polyimide resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 10 wt%. After complete mixing, the mixture was degassed and set aside. The mixed resin was uniformly extruded and coated on the polyimide base film by a casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0044] Example 4 Under nitrogen protection, the diamine monomer 4,5-BIA was dissolved in NMP, stirred at room temperature, and after it was completely dissolved, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 4 / 3, the reaction temperature was 5 ℃, the reaction was carried out for 12 h, and the reaction temperature was increased to 170 ℃ for 10 h to synthesize the polyimide resin I terminated with an amine group. Similarly, under nitrogen protection, the diamine monomer 3, 4-ODA was dissolved in NMP, stirred at room temperature, and after it was completely dissolved, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 3 / 4, the reaction temperature was 5 ℃, the reaction was carried out for 12 h, and the reaction temperature was increased to 170 ℃ for 10 h to synthesize the polyimide resin II terminated with anhydride. Resin I and resin II were mixed in equal molar ratios, and the reaction temperature was controlled at 20 ℃ under nitrogen protection for 12 h to obtain a viscous thermoplastic polyimide resin, which was fully matured, filtered, and degassed for use. The synthesized thermoplastic polyimide resin was mixed with the PMR polyimide resin, and the content of the thermosetting resin was controlled to be 10 wt%. After the mixture was completely mixed, the mixture was degassed and set aside. The mixed resin was uniformly extruded and coated on the polyimide base film by the casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.5 M KOH for 3 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0045] Comparative Example 1 Under nitrogen protection, the diamine monomer 4, 5-BIA was dissolved in NMP and stirred at room temperature. After it was completely dissolved, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 1 / 1. The reaction temperature was 5 ℃, and the reaction was carried out for 12 h. The reaction temperature was then raised to 170 ℃ for 10 h to synthesize the polyimide resin. After sufficient aging, filtration, and degassing, it was set aside. The synthesized polyimide resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 15 wt%. After complete mixing, degassing was carried out for use. The mixed resin was uniformly extruded and coated on the polyimide base film by the casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0046] Comparative Example 2 Under nitrogen protection, the diamine monomer 3,4'-diaminodiphenyl ether (3, 4-ODA) was dissolved in NMP and stirred at room temperature. After complete dissolution, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 1 / 1. The reaction temperature was 5 ℃, and the reaction was carried out for 12 h. The reaction temperature was then raised to 170 ℃ and the reaction was carried out for 10 h to synthesize the thermoplastic polyimide resin. After sufficient aging, filtration, and degassing, it was set aside. The synthesized thermoplastic polyimide resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 15 wt%. After complete mixing, degassing was carried out for use. The mixed resin was uniformly extruded and coated on the polyimide base film by the casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide adhesive film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0047] Comparative Example 3 Under nitrogen protection, the diamine monomer 4, 5-BIA was dissolved in NMP and stirred at room temperature. After it was completely dissolved, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 4 / 3. The reaction temperature was 5 °C, and the reaction was carried out for 12 h. The reaction temperature was then increased to 170 °C for 10 h to synthesize the polyimide resin I terminated with an amine group. Similarly, under nitrogen protection, the diamine monomer 3, 4-ODA was dissolved in NMP and stirred at room temperature. After it was completely dissolved, the dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 3 / 4. The reaction temperature was 5 °C, and the reaction was carried out for 12 h. The reaction temperature was then increased to 170 °C for 10 h to synthesize the polyimide resin II terminated with anhydride. Resin I and resin II were mixed in equal molar ratios and reacted for 12 h under nitrogen protection at a reaction temperature of 20 °C to obtain a viscous thermoplastic polyimide resin, which was fully matured, filtered, and degassed for use. The synthesized resin was uniformly extruded and coated on a polyimide base film by a casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was composited with the polyimide film at 350 °C and a pressure of 1.0 kN to obtain a composite copper foil product.

[0048] Comparative Example 4 Under nitrogen protection, equimolar diamine monomers 4, 5-BIA and 3, 4-ODA were dissolved in NMP and stirred at room temperature. After complete dissolution, dianhydride monomer ODPA was added in an equal amount to the diamine. The reaction temperature was 5 ℃ and the reaction was continued for 12 h. The reaction temperature was then raised to 170 ℃ for 10 h to obtain a random copolymerized thermoplastic polyimide resin. After sufficient aging, filtration and degassing, the mixture was used for standby. The synthesized thermoplastic polyimide resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 15 wt%. After complete mixing, the mixture was degassed and used for standby. The mixed resin was uniformly extruded and coated on the polyimide base film by casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure to obtain a composite copper foil product.

[0049] Comparative Example 5 Under nitrogen protection, diamine monomer 4, 5-BIA was dissolved in NMP, stirred at room temperature, and after complete dissolution, dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 4 / 3, the reaction temperature was 5 ℃, and the reaction was carried out for 12 h to synthesize polyamic acid resin I terminated with amine groups. Similarly, under nitrogen protection, diamine monomer 3, 4-ODA was dissolved in NMP, stirred at room temperature, and after complete dissolution, dianhydride monomer ODPA was added, and the molar ratio of diamine / dianhydride monomer was controlled to be 3 / 4, the reaction temperature was 5 ℃, and the reaction was carried out for 12 h to synthesize polyamic acid resin II terminated with acid anhydride. Resin I and resin II were mixed in equal molar ratios, and the reaction temperature was controlled at 20 ℃ under nitrogen protection for 12 h to obtain a viscous thermoplastic polyamic acid resin, which was fully matured, filtered, and defoamed for use. The synthesized thermoplastic polyamic acid resin was mixed with bismaleimide resin, and the content of thermosetting resin was controlled to be 15 wt%. After complete mixing, the mixture was degassed and set aside. The mixed resin was uniformly extruded and coated on the polyimide base film by casting method, and the thickness of the resin layer was controlled to be 5 μm. The copper foil treated with 0.3 M NaOH for 1 min was compounded with the polyimide film at 350 ℃ and 1.0 kN pressure, and further imidization reaction was carried out at 350 ℃ for 30 min to obtain a composite copper foil product.

[0050] The properties of the polyimide adhesive film composite copper foil prepared in Examples 1-4 and Comparative Examples 1-5 are listed in Table 1.

[0051]

[0052] From the data analysis of Table 1, it can be seen that Examples 1-4 prepared polyimide film composite copper foil with low bubble rate, high adhesion and dimensional stability and good mechanical properties. Compared with Example 1, the thermoplastic polyimide resin synthesized in Comparative Example 1 does not contain a soft segment with a flexible ether bond, so the softening effect after heating is not good, the bonding force with the copper foil is low, and the tensile mechanical properties are directly lower than those of Example 1; the thermoplastic resin in Comparative Example 2 is composed only of a soft segment containing an ether bond, lacks a hydrogen bond network structure, resulting in low peel strength and tensile strength, and poor dimensional stability; Comparative Example 3 does not add a thermosetting polyimide resin, and fails to form an interpenetrating network, so the tensile strength and dimensional stability of Comparative Example 3 are both lower than those of Example 1; the thermoplastic resin with a random copolymer structure synthesized in Comparative Example 4 does not form a microphase separation structure, which makes it difficult to soften the resin when heated, and the bonding with the copper foil is poor, and the peel strength is low; Comparative Example 5 is processed using polyamic acid, a precursor of the thermoplastic polyimide resin, and an imidization reaction occurs simultaneously during the composite process with the copper foil to release by-products, so the bubble rate of the polyimide film composite copper foil prepared in Comparative Example 5 is significantly higher.

[0053] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.

Claims

1. A block structure thermoplastic polyimide resin, characterized in that: The block structure thermoplastic polyimide resin is obtained by sequentially polymerizing a dianhydride monomer Ar with a diamine monomer R1 and a diamine monomer R2. The general structural formula of the resin is shown below: ; Wherein, the dianhydride monomer Ar is one of the following dianhydrides: ; The diamine monomer R1 is one of the following diamines: ; The diamine monomer R2 is one of the following diamines: ; Wherein, m=2-8 and n=2-8 of the block structure thermoplastic polyimide resin.

2. The block structure thermoplastic polyimide resin according to claim 1, characterized in that: The block structure thermoplastic resin consists of a hard segment containing benzimidazole or amide units and a soft segment containing flexible ether bonds, wherein the molar fraction ratio of the hard segment is (30-50) mol%.

3. The method for preparing the block structure thermoplastic polyimide resin according to any one of claims 1 to 2, comprising: Dissolve the diamine monomer R1 and the diamine monomer R2 in a solvent and react with the dianhydride monomer Ar in batches; Wherein, the solvent is selected from one or a combination of N,N-dimethylacetamide, N-methyl-pyrrolidone or γ-butyrolactone.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the diamine monomer R1 to the dianhydride monomer Ar is (m+1) / m; the molar ratio of the diamine monomer R2 to the dianhydride monomer Ar is n / (n+1).

5. A resin composition comprising: The block structure thermoplastic polyimide resin and the thermosetting polyimide resin according to any one of claims 1 to 2, wherein the thermosetting resin is selected from any one of bismaleimide resin and PMR type polyimide resin or a combination of both.

6. The resin composition according to claim 5, characterized in that The mass fraction of the thermosetting polyimide resin in the resin composition is (10-20) wt%.

7. The method for preparing the resin composition according to any one of claims 5 to 6, characterized in that: The preparation method comprises: fully mixing the block structure thermoplastic polyimide resin and the thermosetting polyimide resin according to any one of claims 1 to 2.

8. A polyimide film, characterized in that: The resin composition according to any one of claims 5 to 6 is coated on the surface of a polyimide base film by a cast extrusion method, and then baked and dried to obtain the polyimide adhesive film.

9. A polyimide film composite copper foil, characterized in that: The polyimide adhesive film according to claim 8 is compounded with copper foil by rolling.

10. The polyimide film composite copper foil according to claim 9, characterized in that: The rolling temperature is 300-400°C, the rolling pressure is 0.5-1.0 kN, and the rolling speed is 1.0-1.5 m / min.

Citation Information

Patent Citations

  • A glue-free single-sided panel, its preparation method, and a glue-free double-sided panel containing the same.

    CN113347783B

  • Non-adhesive single-sided flexible copper-clad plate and preparation method thereof

    CN118574306A

  • Novel electronic-grade polyimide film with low linear expansion coefficient and manufacturing method thereof

    CN103524767A

  • ODPA-type fluorine-containing branched polyimide resin film and preparation method thereof

    CN106519674A

  • Polyimide precursor and application thereof

    CN113307971A

Cited By

  • Polyimide-based insulating resin with high stability and high adhesive force and preparation method thereof

    CN121022096A

  • Soluble thermoplastic polyimide resin and preparation method thereof, coating, composite film and flexible copper-clad plate

    CN121086234A

  • Soluble thermoplastic polyimide resin, method for producing the same, coating, composite film, and flexible copper clad laminate

    CN121086234B

  • Method for preparing polyimide material through aqueous phase polymerization

    CN121405941A

  • A method for preparing polyimide materials by aqueous phase polymerization

    CN121405941B